How to land on Earth. From critical zones to the terrestrial - Babo, Constança (2022)
The oeuvre Critical Zones. The Science and Politics of Landing on Earth addresses the climate crisis mainly through the few-kilometers thick layer of critical zones that surrounds planet Earth, within the scope of New Climate Regimes. It proposes the redefinition of concepts such as Gaia, and suggests new ones, namely Terrestrial. The book is the product of a collective endeavor from scientists, artists, philosophers, historians, and activists, arguing that areas, disciplines and all living beings are connected. While associated with the ongoing scientific project Critical Zone Observatories, it was developed and launched during the exhibition Critical Zones - Observatories for Earthly Politics, in May 2020 at ZKM Karlsruhe, and edited by its two main curators, Bruno Latour and Peter Weibel. This review will introduce an impressively complete work, whose reading is as stimulating as necessary, and which contributes remarkably to what will be the most important debate of our century.